The Accounting Policy of Insurance Companies in the Face of the Solvency II Directive and ifrs 4 phase II - Spigarska, Ewa (Studia Oeconomica Posnaniensia, 2015)
The objective of this article is to highlight the problems which insurance companies will face when developing their accounting policy in relation to the planned changes in the International Financial Reporting Standards affecting insurers (IFRS 4 Phase II, IFRS 9) and also changes in the Solvency II directive. Unfortunately regulations in this regard do not coincide in many cases, which will result in a variety of financial information in reports for the purpose of accounting laws and reports prepared for the purpose of solvency. Insurance companies, if possible, should apply uniform principles for recognizing and measuring individual financial operations. However, there may be differences, which will be indicated in this article.